Além da recepção: o papel estratégico do profissional administrativo em saúde no acolhimento e na humanização dos pacientes em uma instituição pública de saúde - Neuzilene da Silva Ximenes; Lucely Lopes Passos de Fernandes; Roberio Rebouças da Silva; Andreza Schmidt Menezes de Souza; Vivianne Karol Gomes Palha; Francisca Rosilene Mendes Lima; Eliane Peixoto; Maria Ezilene Soares Barauna; Merciceide Najar de Souza; Maria Alciete Vieira Souza Lima (Revista ft, 2026)
Humanization of care is one of the foundations for improving the quality of public health services and involves not only professionals directly responsible for clinical care but also all workers participating in the user's journey through healthcare institutions. In this context, healthcare administrative professionals occupy a strategic position, as they frequently represent the first point of contact between patients, their families, and the health service. This study aims to analyze the role of administrative professionals in patient reception and humanization within public healthcare institutions, highlighting their contribution to communication, guidance, organization of patient flows, access to services, resolution of demands, and the development of relationships based on respect, ethics, and dignity. This is a narrative literature review with a qualitative, descriptive, and exploratory approach, based on official documents and scientific publications concerning humanization, patient reception, healthcare management, and user experience. The analysis indicates that limiting administrative work to bureaucratic activities overlooks its participation in the production of care. The way users are received, listened to, informed, and directed can influence their perception of institutional quality, safety, trust, and continuity of care. However, challenges include work overload, insufficient training, communication failures, fragmentation between administrative and clinical sectors, and limited recognition of these workers within institutional humanization strategies. It is concluded that investing in the training, recognition, and integration of administrative professionals into healthcare teams can contribute to transforming reception areas into effective spaces of welcoming care, strengthening humanization and the quality of public health services.